2020
DOI: 10.1186/s12885-020-07314-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of intravitreal chemotherapy-assisted endoresection in monocular patients with group D retinoblastoma

Abstract: Background: This study aimed to determine the efficacy and complications of intravitreal chemotherapy-assisted endoresection for refractory International Classification of Retinoblastoma (ICRB) group D retinoblastoma in monocular patients. Methods: In this retrospective case series, intravitreal chemotherapy-assisted endoresection by pars plana vitrectomy was performed in 11 eyes with refractory ICRB group D retinoblastoma unresponsive to standard therapies in monocular patients. Results: Across a mean follow-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A subsequent study demonstrated IVitC as a promising method for the treatment of vitreous seeds (41). Recently, it has been reported that intravitreal chemotherapy combined with endoresection seems to be safe and effective in globe-salvaging for eyes with refractory group D (42). In addition, with the increasing attention having been paid to the clinical use of anti-VEGF (vascular endothelial growth factor) agents in the patients with eye disease (43), a retrospective review suggested that intravitreal anti-VEGF contributed to a globe salvage rate of 51%, indicating the potential of intravitreal anti-VEGF in the conservative treatment of retinoblastoma (44).…”
Section: Focus In Retinoblastoma Researchmentioning
confidence: 99%
“…A subsequent study demonstrated IVitC as a promising method for the treatment of vitreous seeds (41). Recently, it has been reported that intravitreal chemotherapy combined with endoresection seems to be safe and effective in globe-salvaging for eyes with refractory group D (42). In addition, with the increasing attention having been paid to the clinical use of anti-VEGF (vascular endothelial growth factor) agents in the patients with eye disease (43), a retrospective review suggested that intravitreal anti-VEGF contributed to a globe salvage rate of 51%, indicating the potential of intravitreal anti-VEGF in the conservative treatment of retinoblastoma (44).…”
Section: Focus In Retinoblastoma Researchmentioning
confidence: 99%